(untitled) (Belas Infiéis, 2014)
This study is an attempt to document the problematic nature of an intermediary linguistic system, the lingua franca used by the scientific community, on the production and impact of science from the broad area beyond the inner circle of native English speakers. To this end, a random cross-sectional sample (n=5) of current English-language articles from top-ranked journals in the Brazil-based metapublisher Scientific Electronic Library Online (SciELO) was examined for grammatical issues, especially nominative group construction. In the studied sample, varying and in some cases elevated levels of L1 interference were found, indicating that on the best collective level, there are proficiency problems with the lingua franca, that these problems are not evenly distributed and that systematic language management yielded vastly different language quality outcomes.